1980
DOI: 10.2165/00003088-198005040-00006
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentration and Clinical Effect in Imipramine Treatment of Childhood Enuresis

Abstract: The relationship between steady-state plasma concentraton and clinical effect of imipramine in the treatment of nocturnal enuresis was studied in 22 hospitalised children. After 1 week on placebo the children were given imipramine in a fixed dose of about 1 mg/kg for 3 weeks. The enuresis frequency decreased significantly from the placebo to the first week on imipramine, but then no further improvement was observed. There was a significant correlation between steady-state plasma concentration of desipramine or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Further study is required for clarification of the mechanisms and the magnitude of the alterations observed since it cannot be clearly established from the data collected here. Moreover the scarce number of similar studies, and the discrepancies found among them, make it difficult for us to compare our results with others (Jorgensen et al, 1980;Kolvin et al, 1973;Meadow, 1974). Besides, the variables chosen and the methodology used in each study are different.…”
Section: Discussionmentioning
confidence: 72%
“…Further study is required for clarification of the mechanisms and the magnitude of the alterations observed since it cannot be clearly established from the data collected here. Moreover the scarce number of similar studies, and the discrepancies found among them, make it difficult for us to compare our results with others (Jorgensen et al, 1980;Kolvin et al, 1973;Meadow, 1974). Besides, the variables chosen and the methodology used in each study are different.…”
Section: Discussionmentioning
confidence: 72%
“…Kales et al [18] reported that the enuretic effects of imipramine appear to be independent of its effects on sleep stage. The clinical response has been shown to correlate with plasma levels [19]. Imipramine undergoes significant first-pass metabolism through the liver and so the bioavailability varies by about 29-77% [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, the available data for IMI in paediatric populations are the elimination half-life (tl/2), mean serum levels, drug/metabolite ratio (IMI/DMI), leveb/dose (L/D) ratio and interindividual variability [6,[21][22][23], they all have evident limitations in the establishment of dosage schedules that will guarantee safe and efficient drug levels throughout treatment. The results found there for these parameters (h/2 = 16.3 h, IMI/DMI = 0.99) are in agreement with those reported by others.…”
Section: Discussionmentioning
confidence: 99%